Climate exposure maps to develop a climate gradient for coffee (Peru, Central America, Uganda) and cocoa (Ghana, Ivory Coast, Central America and Dominican Republic) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Use of this innovation by next users documented in Ghana, Ivory Coast, Peru, Central America, Dominican Republic and Uganda.